Evaluation of synchronous multiple primary superficial laryngo-pharyngeal cancers that were treated by endoscopic laryngo-pharyngeal surgery. Issue 6 (December 2021) - Ohno, Kazuchika; Kawada, Kenro; Sugimoto, Taro; Kiyokawa, Yusuke; Kawabe, Hiroaki; Takahashi, Ryosuke; Koide, Nobuaki; Tateishi, Yumiko; Tasaki, Akihisa; Ariizumi, Yosuke; Asakage, Takahiro
Abstract: Objective: ndoscopic laryngopharyngeal surgery (ELPS) is a useful surgery for superficial cancers of the head and neck region, but it has not yet been well evaluated for synchronous multiple primary cancers (multiple primaries). The purpose of this study was to clarify the safety and usefulness of ELPS for patients with multiple superficial primary cancers in the head and neck region. Methods: rom December 2009 to December 2016, 145patients with superficial head and neck cancers underwent ELPS. The patients were divided into two groups; a group consisting of patients with a single primary cancer (single primary) and another group consisting of patients with synchronous multiple primaries, and the incidences of postoperative complications and lymph node metastasis were retrospectively compared between the two groups. Results: f the 145 patients, 107 had a single primary cancer and 38 had multiple primaries. There was no significant difference in the age, sex, or rate of intraepithelial cancer between the two groups. Postoperative complications included dysphagia in 6 (5.6%) patients with a single primary and 2 (5.3%) patients with multiple primaries. One patient with multiple primaries required gastrostomy because of aspiration pneumonia. In addition, the following complications were also observed. Laryngeal paralysis occurred in 2 (1.9%) patients with a single primary, and 1 (2.6%) patient with multiple primaries; tracheostomy because of postoperative bleeding in 1 (0.9%) patient with a single primary; infection occurred in 2 (5.3%) patients with multiple primaries. Postoperative lymph node metastasis was found in 7 (6.5%) patients with a single primary and 6 (15.8%) patients with multiple primaries. Lymphatic invasion of the primary cancer was noted in 3 (2.8%) patients with a single primary and 5 (13.2%) patients with multiple primaries, being significantly higher in the latter group. Conclusion: ELPS is also a safe surgery for patients with multiple primaries. However, the incidence of lymphatic invasion of the primary cancer was significantly higher in patients with multiple primaries.